Enriching s4U‐RNA Using Methane Thiosulfonate (MTS) Chemistry. Issue 4 (7th December 2016) - Duffy, Erin E.; Simon, Matthew D.
Abstract: Metabolic labeling of cellular RNA is a useful approach to study RNA biology. 4‐Thiouridine (s 4 U) is a convenient nucleoside for metabolic labeling because it is cell permeable and is incorporated into newly transcribed RNA, and the sulfur moiety provides a handle for biochemical purification. However, a critical step in the purification of s 4 U‐RNA is the efficiency of the chemistry used to enrich s 4 U‐RNA. Here, we present a protocol for s 4 U‐RNA enrichment that includes efficient and reversible covalent chemistry to biotinylate s 4 U‐RNA using the activated disulfide methane thiosulfonate conjugated to biotin (MTS‐biotin), followed by enrichment on streptavidin beads. The efficiency of this chemistry reduces enrichment bias and requires less starting material, thereby expanding the utility of s 4 U to study RNA biology. © 2016 by John Wiley & Sons, Inc.